Behavior of mixed pea-whey protein at interfaces and in bulk oil-in-water emulsions. (October 2022) - Grasberger, Katherine; Sunds, Anne Vuholm; Sanggaard, Kristian Wejse; Hammershøj, Marianne; Corredig, Milena
Abstract: Due to the growing interest in creating mixed plant-dairy protein emulsion-based foods, it is important to understand how to include plant-dairy protein mixes in existing and new formulations. The aim of this work was to study the dynamics occurring at the oil-water interface in systems containing mixtures of pea and whey protein isolates. By using drop tensiometry combined with bulk-phase exchange, we compared the interfacial dynamics and viscoelastic properties of plant-dairy protein interfaces formed through simultaneous or sequential adsorption. Differences in the adsorption isotherm and interfacial behaviors suggest different interfacial structures for simultaneous and sequential addition. These results were supported by changes in the interfacial composition observed in bulk emulsions. Bulk emulsions prepared with simultaneous adsorption of whey and pea protein isolate showed the lowest creaming stability. The results show how different emulsion properties can be achieved using the same protein mixtures by fine tuning their interfacial composition to reach maximum product functionality. Graphical abstract: Unlabelled Image Highlights: Both pea and whey readily adsorb at oil-water interfaces in mixed systems. The colloidal state of pea proteins strongly impacts their interfacial behavior. Pea and whey protein isolates form viscoelastic interfaces. Altering the order of protein addition affects the final interfacial properties. Simultaneous addition of pea and whey proteins may cause emulsion instability.